What is a Wilton scraper? Perspectives from the Late Holocene assemblage of Balerno Main Shelter, Limpopo Province, South Africa - (:unkn) unknown (My University, 2019)
Microlithic Wilton scrapers are widespread stone tools of the southern African Holocene Later Stone Age. Though they have been studied and classified in various ways, there are still many uncertainties regarding their fabrication, function and hafting, which ultimately produce one question: are all these scrapers the same tool? The scraper variability in one site, Balerno Main Shelter in the Limpopo Province of South Africa, is investigated through a morpho-functional analysis of the Late Holocene (end-)scraper assemblage. The results of our analysis led us to individualise three types of tool that vary primarily with regard to the characteristics of their passive units (the assumed prehensile part). This classification is accompanied by hypotheses about the hafting and functioning of these scrapers, and carries implications for the categorisation of Wilton scrapers throughout southern Africa.
Keywords: African Research